Ответы и объяснения

2013-04-06T09:19:06+00:00

Ты где-то ошибся перерешиваю

Отмечаем ОДЗ

\begin{cases} x^2+2x+4\neq0\\x^3-8\neq0\\x-2\neq0 \end{cases}

Решаем уравнение

\frac{3x+2}{x^2+2x+4}+\frac{x^2+39}{(x-2)(x^2+2x+4)}-\frac{5}{x-2}=0 \\ \frac{(3x+2)(x-2)+(x^2+39)-5(x^2+2x+4)}{(x-2)(x^2+2x+4)}=0 \\ \frac{3x^2-4x-4+x^2+39-5x^2-10x-20}{(x-2)(x^2+2x+4)}=0 \\ \frac{x^2+14x-15}{(x-2)(x^2+2x+4)}=0 \\ x^2+14x-15=0 \\ D=b^2-4ac=14^2-4*1(-15)=256 \\ \left \{ {{x=\frac{-14-16}{2}=-15} \atop {x=\frac{-14+16}{2}=1}} \right.

Ответы удовлетворяют ОДЗ

Ответ: x=-15, x=1